Pharmacy OSCEs and Competency-Based Assessments by Sharon Haughey and Roisin O'Hare - Saima Afzal (British Journal of Pharmacy, 2018)
Over the past decade, the pharmacists’ role has been revolutionised utilising and incorporating expert clinical skills and knowledge. In doing so, a pharmacist’s performance is underpinned by competence and must be assessed in a valid and reliable manner throughout the undergraduate degree and preregistration year prior to becoming a responsible practitioner. The Observed Structured Clinical Examination (OSCE) is a practical assessment method evaluating student application of knowledge and understanding of the content in a simulated real-life environment. ‘Pharmacy OSCEs and competency-based assessments’ by Haughey and O’Hare is a novel book which endeavours to enhance the use of this method of assessment in pharmacy education.